2017
DOI: 10.1530/erc-17-0085
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s thyroiditis predicts outcome in intrathyroidal papillary thyroid cancer

Abstract: Hashimoto's thyroiditis (HT) seems to have favourable prognostic impact on papillary thyroid cancer (PTC), but data were obtained analysing all disease stages. Given that HT-related microenvironment involves solely the thyroid, we aimed to assess the relationship between HT, as detected through pathological assessment, and outcome in intrathyroidal PTC. This was a multicentre, retrospective, observational study including 301 PTC with no evidence of extrathyroidal disease. Primary study endpoint was the rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 42 publications
1
41
0
1
Order By: Relevance
“…The main characteristics of the 71 articles included in this meta-analysis are summarized in Table 1 [ 7 8 9 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 ]. A total of 44,034 participants with PTC were enrolled, of whom 11,132 (25.3%) had HT.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the 71 articles included in this meta-analysis are summarized in Table 1 [ 7 8 9 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 ]. A total of 44,034 participants with PTC were enrolled, of whom 11,132 (25.3%) had HT.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the prognosis for thyroid lymphoma depends on staging, and early diagnosis is of vital importance [17][18][19][20][21]. When patients have coexistent HT with a rapidly growing thyroid mass or with symptoms of obstruction, a likely diagnosis may be HT with or without malignant lymphoma [22]. Ultrasound is a widely accepted diagnostic method for examining thyroid [23][24][25][26][27], but several studies have reported that it is less useful in differentiating between PTL and HT [28].…”
Section: Discussionmentioning
confidence: 99%
“…Irrespectively of whether HT is etiologically linked to PTC or merely judged "guilty by association," the importance of this coexistence lies on its clinical significance. Since a complex immune network has been considered a core component of PTC microenvironment, it is rational to assume that HT-the epitome of aberrant immune reaction-influences the progression of coexistent PTC [105]. In that respect, the positive association of a favorable outcome of coexistent PTC with HT, tumor-associated macrophage infiltration, and CD8+ lymphocytes highlights the antitumor potential of the immunological landscape intrinsic in HT [106].…”
Section: Effect Of Ht On Coexistent Ptc: Host Protective or Tumor Promentioning
confidence: 99%
“…The results of a recent meta-analysis including 71 published studies with 44,034 participants revealing that PTC coexistent with HT significantly correlated with reduced incidence of extrathyroidal extension, lymph node, and distant metastasis and increased recurrence-free survival duration compared with PTC alone are seminal [47]. Noticeably, the coexistence of HT with PTC has been proven an independent indicator of favorable prognosis of PTC [105], irrespectively of the extent of lymph node dissection [46], though inconsistently [108]. On the other hand, the reported absence of host-protective effect of HT on coexistent PTC [42-45] hampers the endorsement of HT as a prognostic PTC biomarker.…”
Section: Effect Of Ht On Coexistent Ptc: Host Protective or Tumor Promentioning
confidence: 99%